Outcomes of Surgical Management of Distal Femur Fracture with Distal Femoral Locking Compression Plate at Koshi Zonal Hospital - Sah, Shambhu; Karn, Navin Kumar; KC, Bikash; Yadav, Roshan; Dangi, Sailj Jung; Adhikari, Anurag Raj (Birat Journal of Health Sciences, 2018)
Introduction: Distal femoral fractures comprise 4-6% of all femur fractures. The management of distal femur fractures are challenging because of significant morbidity and complication rate even with advanced surgical techniques and implants. Open reduction and internal fixation (ORIF) with pre-contoured distal femoral locking compression plate (DF-LCP) is one of the most acceptable surgical procedures these days.Objectiv: Evaluation of functional outcomes of distal femur fractures managed surgically using DF-LCP at Koshi Zonal Hospital.Methodology: In this cross sectional study 21 patients having closed distal femur fractures with or without intra-articular extension to femoral condyle fixed with DF-LCP at Koshi Zonal Hospital, Nepal from March 2016 to March 2017 were included. Patients with open fracture, severe comminuted fracture, and neurovascular impairment were excluded. These patients were followed-up for up to one year and we recorded the knee range of motion, full weight bearing time fracture union time, and complications. We used Neers' functional scoring system to evaluate the final outcomes and data was analysed using Microsoft Excel Programe.Results: Out of the 21 patients of distal femur fractures, 16 were diametaphyseal distal femur fractures and five were supracondylar fractures with intra-articular extension. Mean age recorded was 45 (range 19-75) years, hospital stay mean duration 12 (range 10-19) days and duration of surgery 85 (range 60-150) minutes, full weight bearing walking time mean 16 (range 12-22) weeks, radiological union time mean 20 (range 17-29) weeks and Neers' score was excellent in 66.66%, satisfactory in 23.80%, unsatisfactory in 4.76%, and poor in 4.76%.None of our patients had complications like; loss of fixation, implant failure or post-operative neurovascular injury.Conclusion: Distal Femoral Locking Plate is one of the best implant to be used as fixation method for both extra-articular and intraarticular distal femur fracture.Birat Journal of Health SciencesVol.2/No.3/Issue 4/Sep- Dec 2017, Page: 260-265